(untitled) (Fiep Bulletin - online, 2012)
It is known that the motor development of the human being is a subject much studied throughout history, many studies have been conducted in order to evaluate the motor evolutionary stages corresponding to their biological maturation. The purpose of this study of descriptive-exploratory character is to verify the assessed indices of motor performance of the individuals with disabilities in evaluations conducted in August and September of 2011. The research involved 32 students enrolled in APAE and participating of the Piracema Project of UNISC- Swimming for People with Special Needs. To collect data it was used the Scale of Motor Development (SMD) kit of Rosa Neto (2002). As result of this study it was verified that the variables assessed, fine and global motricity, balance, body scheme/speed, spatial organization and language / temporal organization motor pattern were classified as “very low”, being the variable fine motricity was the one that most obtained a positive result in the average and the spatial organization the variable with most negative results in the average. Thus, it is concluded taht the chronological age does not influence in the general motor age of the same.